Endoscopic vein harvesting: a guide for approaching difficult cases and assessing patients preoperatively. (30th May 2022) - Siddiqui, Sadiq; Whooley, Jack; Miceli, Antonio; Bartolozzi, Fabio; Soo, Alan
Abstract: Coronary artery bypass grafting remains the most commonly performed cardiac surgical procedure worldwide. The long saphenous vein still presides as the first choice conduit as a second graft in multivessel coronary artery bypass grafting surgery. Traditionally, the long saphenous vein has been harvested with an open approach which can potentially result in significant wound complications in certain circumstances. Endoscopic vein harvesting is a minimally invasive vein harvesting technique, which requires a single 2–3 cm incision and is associated with a quicker return to normal daily activities, decreased wound complications and better quality of life in the longer term. There is a learning curve associated with endoscopic vein harvesting adoption and there are certain patient factors that can prove to be challenging when adopting an endoscopic approach. This commentary aims to provide a concise guide of certain challenging patient factors that operators may encounter during endoscopic vein harvesting, and how to approach these patients in both the preoperative and intraoperative settings. We suggest that with appropriate planning and awareness of the challenging patient factors and problematic venous anatomy that exists, the operator can consistently formulate a strategy for ensuring a successful endoscopic harvest. Abstract : Coronary artery bypass grafting remains the most commonly performed cardiac surgical procedure worldwide [1, 2].